(untitled) (Sebha University Conference Proceedings, 2024)
The aim of this study was to determine effects of Tannato iron (II) and Ascorbato tannato iron (II) on Anemic albino male rats. Anemia was induced by repeated extraction of about 0.6 mL blood daily from caudal vein within 6 consecutive days. Rats with Hemoglobin levels lower than 12g/dL were considered anemic. Twenty of albino male rats that were divided into four groups of 5 rats, including the normal control group, the anemic control group, the anemic group received Tannato iron (II), and the anemic group received Ascorbato tannato iron (II) at dosage 10mg/Kg body weight daily for 30 days. At the end of the study rats were anesthetized and blood was collected to determine complete blood count test, iron metabolism parameters, liver and kidney functions tests, and determine liver, kidney and spleen weight ratio to body weight. The results were shown that the treatment with tested compounds caused improve in anemia state by increase in RBCs, HGB HCT and iron levels. While there were a decrease in TIBC levels although decrease in ferritin levels. And results of liver and kidney function were within normal levels except slight increase in urea and decrease in direct bilirubin. And shown a decrease in liver weight, an increase in kidney weight, and no effects on spleen weight ratio to body weight. And these results indicate that there were no toxic effects of tested iron compounds. And Tannato iron (II) compound had better effects of Ascorbato tannato iron (II) compound.